PDX1 in early pregnancy is associated with decreased risks of gestational diabetes mellitus and adverse pregnancy outcomes - Zhang, Qian; Zhang, Qing-qing; Dong, Shu-qin; Liu, Xia; Wei, Jing; Li, Kai; Lu, Yu (Frontiers in Endocrinology, 2025)
AimTo investigate the association of pancreatic duodenal homeobox-1 (PDX1) in early pregnancy with the risks of gestational diabetes mellitus (GDM) and adverse pregnancy outcomes.MethodsA total of 231 pregnant women were recruited at their initial antenatal care visit during 8-12 gestational weeks in this study. The 75g OGTT was performed during 24-28 gestational weeks. Blood samples were collected to measure PDX1 levels. Participants were followed throughout their pregnancy to monitor for the development of GDM and adverse pregnancy outcomes. The odds ratio (OR) was used to assess the risks of GDM and adverse pregnancy outcomes.ResultsPregnant women in the GDM group had higher levels of HOMA-IR and TyG index, and lower PDX1 levels both in early and mid-pregnancy (P<0.05), but had lower HOMA-β levels only in mid-pregnancy (P<0.05). PDX1 in early pregnancy was negatively correlated with FPG, 2h PG, HOMA-IR, and TyG, while positively correlated with HOMA-β in mid-pregnancy (P<0.05). The adjusted analysis showed that elevated PDX1 levels in early pregnancy were associated with reduced risks of GDM (aOR 0.287, 95%CI 0.130-0.636, P=0.002), macrosomia (aOR 0.249, 95%CI 0.076-0.811, P=0.021) and composite adverse pregnancy outcomes (aOR 0.496, 95%CI 0.256-0.960, P=0.037).ConclusionElevated PDX1 in early pregnancy was associated with decreased risks of GDM and adverse pregnancy outcomes.